2016
DOI: 10.1007/s10689-016-9960-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MSH2 inversion of exons 1–7 in clinical evaluation of families with suspected Lynch syndrome

Abstract: Purpose Traditional germline sequencing and deletion/duplication analysis does not detect Lynch syndrome-causing mutations in all individuals whose colorectal or endometrial tumors demonstrate mismatch repair (MMR) deficiency. Unique inversions and other rearrangements of the MMR genes have been reported in families with Lynch syndrome. In 2014, a recurrent inversion of MSH2 exons 1-7 was identified in five families suspected to have Lynch syndrome. We aimed to describe our clinical experience in identifying f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Genetic testing using multigene panels or whole exome sequencing focuses on the coding sequence, but more recently, application of whole genome sequencing to detect cancer predisposing variation has come to the fore. Most genetic predisposition to cancer relates to sequence variation, but there are other genetic mechanisms which may influence cancer risk, such as methylation defects (constitutional MLH1 hypermethylation [3]), imprinting disorders (e.g., Beckwith-Wiedemann syndrome [4]), and copy-neutral structural rearrangements [5] (e.g., MSH2 inversion [6] and chromosome 3 translocations involving VHL [7]), which are not readily detected by whole genome sequencing.…”
Section: Genetic Variationmentioning
confidence: 99%
“…Genetic testing using multigene panels or whole exome sequencing focuses on the coding sequence, but more recently, application of whole genome sequencing to detect cancer predisposing variation has come to the fore. Most genetic predisposition to cancer relates to sequence variation, but there are other genetic mechanisms which may influence cancer risk, such as methylation defects (constitutional MLH1 hypermethylation [3]), imprinting disorders (e.g., Beckwith-Wiedemann syndrome [4]), and copy-neutral structural rearrangements [5] (e.g., MSH2 inversion [6] and chromosome 3 translocations involving VHL [7]), which are not readily detected by whole genome sequencing.…”
Section: Genetic Variationmentioning
confidence: 99%
“…Germline WGS analysis of the mother-daughter pair SLS11 and SLS12, each with a MSH2/MSH6 deficient CRC, identified an inversion encompassing exons 1-7 of MSH2. This inversion was first reported in the literature by Wagner et al in 2002 37 and later reported by Rhees et al 32 in 2014 and by Mork et al 38 in 2017 using various methods, although none employing WGS. Targeted sequencing of the MMR genes in the two corresponding CRCs (T11A and T12) revealed a single predicted pathogenic somatic MSH2 gene mutation in T12 but not in T11A.…”
Section: Discussionmentioning
confidence: 52%
“…Tumors from LS patients normally exhibit high microsatellite instability (MSI‐H) and loss of expression of one or more MMR proteins 4 . Substitutions, small insertion/deletions, large deletions/duplications, inversions, 5‐7 as well as insertions of retrotransposon have been reported in the MMR genes as causes of LS 8,9 …”
Section: Introductionmentioning
confidence: 99%